2007
DOI: 10.1128/jvi.01768-06
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class I Binding Promiscuity of the CD8 T-Cell Epitopes of Human Papillomavirus Type 16 E6 Protein

Abstract: One of the critical steps in the progression to cervical cancer appears to be the establishment of persistent human papillomavirus (HPV) infection. We have demonstrated that the lack of cytotoxic T-lymphocyte response to HPV type 16 (HPV 16) E6 protein was associated with persistence and that the potential presence of dominant CD8 T-cell epitopes was most frequently found (n ‫؍‬ 4 of 23) in the E6 16-40 region by examining the pattern of CD8 T-cell epitopes within the E6 protein in women who had cleared their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 40 publications
3
43
1
2
Order By: Relevance
“…As an experimental support to our prediction, Nakagawa et al 2004;Nakagawa et al 2007 reported a region from 52 to 61 (FAFKDLCIVY) of HPV 16 E6 protein and Rudolf et al (2001) reported KLPDLCTEL of HPV 18 E6 to be an endogenously processed T-cell epitope. As an extension, we were high risk HPV types.…”
Section: 4167 Prediction Of Promiscuous Epitopes In the E6 Protein Osupporting
confidence: 85%
“…As an experimental support to our prediction, Nakagawa et al 2004;Nakagawa et al 2007 reported a region from 52 to 61 (FAFKDLCIVY) of HPV 16 E6 protein and Rudolf et al (2001) reported KLPDLCTEL of HPV 18 E6 to be an endogenously processed T-cell epitope. As an extension, we were high risk HPV types.…”
Section: 4167 Prediction Of Promiscuous Epitopes In the E6 Protein Osupporting
confidence: 85%
“…Using a method previously developed by our group for characterizing HPV-specific CD8 Tcell epitopes, antigen-specific T-cell clones were isolated and characterized [14,15]. Sufficient cells from the T-cell lines were remaining only for subjects 15-03 and 15-04 to perform this part of the analysis.…”
Section: Selecting and Growing Antigen-specific T-cell Clonesmentioning
confidence: 99%
“…An ELISPOT assay was used to screen for epitope-specific T-cell clones as previously described [15]. Two 15-mer peptide pools (10 µM each peptide) covering the HPV 16 E7 46-70 region and covering the HPV 16 E7 61-85 region, respectively, were used.…”
Section: Screening T-cell Clonesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, E7 7-15 is also able to bind HLA-A2 and -B8 to be recognized by CTL (Oerke et al, 2005;Ressing et al, 1995). From the latter results, two hot spots of CD8+ T-cell epitopes in protein E6 may be located in the regions E6 29-38 and 52-61 and another one in protein E7 (E7 7-15) (Nakagawa et al, 2007). Nevertheless, a poor immunogenicity of E7 protein was observed in many studies during both HPV 16 infection and after peptidic vaccination using long peptides spanning both E6 and E7 Welters et al, 2008) such as those used in our study.…”
Section: How To Determine the Epitopic Regions For A Therapeutic Vaccmentioning
confidence: 63%